Revealing a frame to incorporate safe human behaviour in assembly processes. Issue 11 (2018) - Fruggiero, F.; Fera, M.; Iannone, R.; Lambiase, A.
Abstract: This study deals with the Human Reliability Analysis. A causal methodology is used to report the dynamic responses over time of humans at work. This structure is mounted inside a main framework which includes multi criteria decisions about main and subsidiaries concepts that influence the work-stress and the operations management. Factors and variables from the Human, Team, Work, Environment behavior are considered and declined in constant, measurable and depended elements with inter and intra level connections. Contextualization in a safety based approach is reported as per different tasks in a motor company. Calibration on humans and assembly tasks is reported under a dynamic simulation across levels, auxiliary variables and constants. Critical influencing factors for human reliability at work are identified and modelled.